Survivors of allogeneic bone marrow transplants in childhood report no significant long‐term respiratory symptoms: A single‐center analysis over 20 years. (22nd December 2020) - Ball, Jessica; Growcott, Siona; Cameron, Alison
Abstract: Pulmonary toxicity is documented in long‐term survivors of allogeneic BMT. No studies have specifically evaluated late pulmonary symptomatology in these patients. 85 long‐term pediatric survivors were sent a validated questionnaire of pulmonary symptomatology. Demographic and clinical data were retrospectively collected from the respondents medical records. Response rate was 52.9%. Mean follow‐up post‐BMT of those who responded was 12.3 years. Mean pulmonary symptom scores were low (0.78). There was no significant difference in symptoms between patients who underwent MA conditioning with or without TBI. These results are reassuring that long‐term survivors of pediatric BMT have few respiratory symptoms which do not impact on activities of daily living.